Teachers’ Perception towards the Abolishment of Academic Early Childhood Education in Indonesia - Tartila, Tartila; Taridi, Muhamad (JR-ELT (Journal of Research in English Language Teaching), 2017)
Indonesian government has prohibited academic early childhood education. However, teachers at many kindergartens in Indonesia still give literacy and numeracy to students. The researcher, therefore, was interested in conducting research exploring teachers’ perception towards the abolishment of academic early childhood education in Indonesia. The method of the research was qualitative research by using phenomenological method. The informants of this research were teachers at TK Para Bintang Jambi. In collecting the data the researcher used interview. Through interview, the researcher found that all teachers at this kindergarten appreciate governments policy related to teaching literacy and numeracy prohibition. Unfortunately, they cannot implement the policy due to some reasons. They are because people claim that students in kindergarten are in golden period to grasp knowledge, parents expect their children able to read, write, and count as early as possible, Elementary Schools still carry out enrolment test, and many teachers misunderstand the curriculum demands of early childhood.